ANALISIS TINDAK TUTUR DIREKTIF DALAM PODCAST YOUTUBE RADITIYA DIKA EPISODE “DOKTER TIRTA SEKARANG BERUBAH” - Kusuma, Arum; Wahidy, Achmad; Effendi, Darwin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe certain implicatures in the speech delivered by Raditya Dika and Doctor Tirta in a conversation in a podcast broadcast on Raditya Dika's YouTube channel, in the episode entitled